The Influence of Benthik Traditional Gameson the Level of Sibling Rivalry among Children: A Quasi-Experimental Study - Adinda Putri Sholikhah; Abadina Ukhtisiwi; Lia Kurniawati; Anisya Salsabila Ainun Nur Azizah (Universitas Muhammadiyah Surakarta, 2024)
Abstract.Children's relationships with their siblings encompass a spectrum of experiences, ranging from positive connections to negative interactions. A notable negative facet that can emerge within sibling dynamics is the phenomenon of sibling rivalry. This phenomenon entails the manifestation of competition, jealousy, and animosity among siblings, often arising following the birth of a younger brother or sister.The prevalence of sibling rivalry is associated with adverse outcomes, including heightened anxiety and impaired emotional regulation in children. To address the intricate issue of sibling rivalry, fostering cooperative interactions among siblings has been proposed as a potential solution. This research aims to describe whether the modification of the traditional game